2021
DOI: 10.1136/bmjopen-2021-048702
|View full text |Cite
|
Sign up to set email alerts
|

How patients with COVID-19 managed the disease at home during the first wave in Spain: a cross-sectional study

Abstract: ObjectiveMost patients with mild COVID-19 had to stay at home trying to implement an optimal quarantine. The aim of this study was to describe the COVID-19 cases during the first wave of the pandemic in Spain, how they managed the disease at home, focusing on differences by age, as well as differences in knowledge, attitudes and preventive practices, compared with the uninfected population.DesignAn online survey was used to conduct a cross-sectional study of individuals who were 14 years or older living in Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…However, lower age groups are more likely to feel depressed because of the pandemic, probably due to the impact it has had on their daily activity and social relationships, unlike older people. In addition, pandemic fatigue is higher in younger age groups 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…However, lower age groups are more likely to feel depressed because of the pandemic, probably due to the impact it has had on their daily activity and social relationships, unlike older people. In addition, pandemic fatigue is higher in younger age groups 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of people in various countries reported that their mental health was adversely affected during the first wave of the pandemic [4]. The prevalence of distress was reported to have increased during the second wave in autumn and winter 2020, which coincided with the re-tightening of restrictions to contain the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In other Mediterranean countries, for example Spain, a survey about COVID-19 management at home, carried out on 3398 people, was recently performed [ 37 ]. In their cross-sectional study, the authors reported that, at least at the beginning of the pandemic, antipyretics, hydroxychloroquine and antibiotics were the most frequently used drugs to treat patients with mild symptoms of COVID-19 while staying at their homes during the lockdown [ 37 , 38 ]. Actually, no real COVID-19-targeting therapy was ever appointed within the first months of the pandemic, so physicians most probably were working in the dark.…”
Section: Introductionmentioning
confidence: 99%